RECONSTRUCTION OF CRIMINAL LIABILITY DOCTRINE IN THE ARTIFICIAL INTELLEGENCE ECOSYSTEM IN INDONESIA: ANALYSIS OF NORMS' VAPOR, REINTERPRETATION OF MENS REA AND HYBRID LIABILITY MODEL BASED ON SUBTANTIVE JUSTICE - Agus Priyanto; Fero Sanjaya; Herlita Eryke (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The rapid development of Artificial Intelligence (AI) has transformed the nature of crime from individual-based actions into complex and multi-actor systems, posing significant challenges to Indonesian criminal law. This study aims to analyze the normative gap in criminal liability for AI-based crimes, reinterpret the concept of mens rea , and formulate an adaptive liability model through the Hybrid Criminal Liability approach. This research employs normative legal methods with statutory, conceptual, and comparative approaches. The findings reveal that existing legal frameworks, including the Criminal Code, Law Number 1 of 2024 concerning the Second Amendment to the ITE Law, and Law Number 27 of 2022 concerning Personal Data Protection, are insufficient to address the autonomous and distributed nature of AI-based crimes. This normative gap leads to legal uncertainty, potential impunity, and inadequate victim protection. This study proposes a Hybrid Criminal Liability model that integrates the responsibilities of developers, operators, and users proportionally based on their roles, while also reinterpreting men's reasons through an expanded notion of fault encompassing both intent and systemic negligence. Comparative analysis with the EU Artificial Intelligence Act indicates a global shift toward risk-based, multi-actor liability frameworks. The contribution of this research lies in offering an adaptive, progressive, and substantively just criminal liability doctrine to address AI-driven crimes in Indonesia. KEYWORDS: Artificial Intelligence, Criminal Liability, Mens Rea, Normative Gap, Hybrid Criminal Liability